Transatlantic collection of health informatics competencies - Alpo Värri; Rachelle Blake; Jean Roberts; Susan H. Fenton; Mary Cleary; Scott F. Zacks; Gora Datta; Rachelle Kaye; Jamie Parker; Christina Nguyen; Michelle Dougherty; Nessa Barry; et al. (Finnish Social and Health Informatics Association, 2016)
The electronic collection, processing and management of information is becoming increasingly important in healthcare. Because of the nature of the healthcare provision and delivery process, where the health, safety and quality of human lives are impacted on a daily basis, it is critical that those who work in the field are competent and able to perform all clinical, administrative, research and technology-impacted facets of their roles. The United States and the European Union have been working to encourage broader and more effective use of Information and Communications Technology (ICT) within healthcare. The development, use and governance of ICT within healthcare, often called health informatics, requires a number of competences which need to be identified and integrated into relevant skills assessment, education and training. Ultimately, this will help produce a more proficient and a more confident mobile health informatics-empowered workforce. A structured set of health information technology and eHealth implementation competences was collected in a co-operation project by voluntary experts in USA and European Union. The project took a deliberately broad starting point, seeking and reviewing an extensive range of related competencies. The skills cover the following domains of professions working with health information technology: direct patient care; administrative; engineering/information, communication, and technology (ICT); informatics; and research and biomedicine. The aggregation of over one thousand competencies was classified to a baseline set of skills and four levels of expertise in 33 focus areas according to Bloom's taxonomy. The data set also contains definitions of 268 'typical' professional roles. The use of the collection of competencies is supported by an open access web tool through which all the competencies can be searched through a query mechanism. The limitation of this work is that only the Acute Care segment of roles and competencies impacted by ICT was evaluated within the scope of this project, however, this subset of other care settings such as ambulatory, rehabilitative care, surgery, and others serves as a representative set of roles and competencies within the health care field as well as a being an important proof of concept for future usefulness of the work if extended beyond its current span. This project has made a contribution to the potential improvement of workforce mobility internationally.